EFEKTIVITAS PENGGUNAAN MULTIMEDIA INTERAKTIF BERBASIS STORRYTELLING UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA KELAS V SEKOLAH DASAR - Friesca Adelia Riyadi; Alfi Laila; Vira Karunia Putri (STKIP Subang, 2026)
The low level of numeracy literacy among elementary school students, particularly in understanding number operations, highlights the need for more engaging and meaningful instructional innovations that align with learners’ developmental characteristics. Interactive multimedia based on storytelling emerges as a strategic alternative because it integrates narrative, visual elements, and digital interactivity to strengthen conceptual understanding and enhance learning motivation. This study aims to 1) analyze the effectiveness of storytelling-based interactive multimedia in improving students’ numeracy literacy; and 2) identify the factors influencing its successful implementation. This research employs a Systematic Literature Review (SLR) using a qualitative descriptive approach to synthesize ten selected articles obtained through the PRISMA 2020 stages, including identification, screening, and inclusion. The studies reviewed involve elementary school students, particularly those in grade V, within the context of mathematics learning. Data were analyzed by examining the alignment of research questions, key findings, and implications reported in each article regarding the development of numeracy skills. The results of the study indicate that 1) interactive multimedia based on storytelling is effective in enhancing students’ understanding of numeracy concepts, learning engagement, and motivation; and 2) infrastructure readiness and teacher competence significantly influence the smooth implementation of digital media, with schools that have adequate technological support demonstrating higher numeracy outcomes. This study recommends the development of more adaptive narrative-based media that can be seamlessly integrated into mathematics instruction.